Theoretical investigations and simulations of femtosecond stimulated Raman spectroscopy and coherent anti-stokes Raman spectroscopy - Li, Xiuting (2013)
Femtosecond stimulated Raman spectroscopy (FSRS) and coherent anti-Stokes Raman spectroscopy (CARS) as the novel techniques are widely employed to study the molecular structure and chemical reaction dynamics of physical and biological processes that occur on the ultrafast femtosecond time scale. Especially, FSRS possesses many advantages: simultaneous high temporal and spectral resolutions, free of fluorescence background, high signal-to-noise ratio, wide vibrational spectrum range and rapid data acquisition. The research in this thesis aims to provide a quantum mechanical investigation of FSRS and CARS. A multidimensional separable displaced harmonic oscillators model is used to derive analytical expressions for the third-order polarizations. The FSRS of rhodamine 6G (R6G) simulated with a delta function probe pulse and the inverse Raman scattering (IRS) process of crystal violet (CV) have been investigated by the perturbative quantum wave packet theory. Twenty four Feynman dual time line and four wave mixing energy level diagrams are first presented to depict CARS. The line-shape and relative intensity of each term are interpreted for both off-resonance CARS and resonance CARS on toluene and R6G, respectively.